Landscape in Geography Education. An Analysis of the Curriculum Contents of Spanish Primary and Compulsory Secondary Education - Fernández-Álvarez, Rubén (Journal of Geography Education, 2020)
The teaching of Geography in Spain has traditionally been part of the curricula that have ordered the different stages of education. One of the traditional ways of undertaking the teaching-learning process of this discipline was through the use of the landscape as an instrument and tool of support. This paper aims to analyze the curricular documents of primary education and secondary education to quantify and characterize the contents centered on the landscape that appear in them. The curricular analysis aims also to relate landscape content to the postulates of the European Landscape Convention (ELC) in order to identify if there is agreement between compulsory education (aspects centered on the landscape) and the postulates emanating from the Convention.